IL4I1 binds to TMPRSS13 and competes with SARS-CoV-2 spike - Gatineau, Jérôme; Nidercorne, Charlotte; Dupont, Aurélie; Puiffe, Marie-Line; Cohen, José L.; Molinier-Frenkel, Valérie; Niedergang, Florence; Castellano, Flavia (Frontiers in Immunology, 2022)
The secreted enzyme interleukin four-induced gene 1 (IL4I1) is involved in the negative control of the adaptive immune response. IL4I1 expression in human cancer is frequent and correlates with poor survival and resistance to immunotherapy. Nevertheless, its mechanism of action remains partially unknown. Here, we identified transmembrane serine protease 13 (TMPRSS13) as an immune cell-expressed surface protein that binds IL4I1. TMPRSS13 is a paralog of TMPRSS2, of which the protease activity participates in the cleavage of SARS-CoV-2 spike protein and facilitates virus induced-membrane fusion. We show that TMPRSS13 is expressed by human lymphocytes, monocytes and monocyte-derived macrophages, can cleave the spike protein and allow SARS-CoV-2 spike pseudotyped virus entry into cells. We identify regions of homology between IL4I1 and spike and demonstrate competition between the two proteins for TMPRSS13 binding. These findings may be relevant for both interfering with SARS-CoV-2 infection and limiting IL4I1-dependent immunosuppressive activity in cancer.